Sowing the drops of change: Transforming lives in the Sahel amidst climate adversity - Kinyua, Michael; Mwangi, Obadiah (2024)
Transforming lives in the Sahel, the AVENIR project provides training and sustainable technologies for resilient and prosperous agriculture.